Alopecia in Association with Malignancy: A Review - Poonkiat Suchonwanit (2019)
© 2018, Springer Nature Switzerland AG. The interaction between hair and malignancy is complicated. Various hair abnormalities can manifest in oncology patients as a clinical manifestation, the result of cancer therapy, or due to a paraneoplastic condition. The mechanisms of these changes remain unclear. Alopecia is one of the common clinical presentations occurring in oncology patients that affects their quality of life. The condition can concomitantly develop during the course of malignancy or when patients undergo cancer treatment. It is important for physicians to understand alopecia in association with malignancy as it may be an important associated finding or provide the clues to aid diagnosis. The aim of this review is to summarize the clinical characteristics of alopecia that occur in cancer patients and their relationship with the type of malignancy and its treatment.